Perlindungan Hukum terhadap Pembeli Beritikad Baik sebagai Pemilik atas Sengketa Objek Tanah Hasil dari Penjualan Lelang (Studi Putusan Mahkamah Agung Nomor 2125 K/PDT/2020) - Muhammad Luthfi Yandi; sutiarnoto; suhaidi (CV Rewang Rencang, 2025)
The sale of auction objects, particularly execution auctions, often triggers disputes between auction buyers and parties claiming rights over the auctioned objects, creating legal uncertainty for good faith buyers. This study analyzes legal protection in disputes over auction object ownership based on Supreme Court Decision Number 2125 K/Pdt/2020 using normative juridical methods with a case study approach. The problem formulation includes procedures land auction sales due to default according to Minister of Finance Regulation Number 93 of 2010, legal protection for good faith buyers after auctions through KPKNL, and analysis of judicial considerations. The study findings indicate that legal protection is guaranteed through recognition of certificates as valid proof of ownership, and judges have applied the principle of legal protection by declaring possession without legal basis as unlawful acts.